2009
DOI: 10.2174/187221009788490040
|View full text |Cite
|
Sign up to set email alerts
|

DNA in the Material World: Electrical Properties and Nano-Applications

Abstract: Contradictory experimental findings and theoretical interpretations have spurred intense debate over the electrical properties of the DNA double helix. In the present review article the various factors responsible for these divergences are discussed. The enlightenment of this issue could improve long range chemistry of oxidative DNA damage and repair processes, monitoring protein-DNA interactions and possible applications in nano-electronic circuit technology. The update experimental situation concerning measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 88 publications
1
11
0
6
Order By: Relevance
“…Notwithstanding experimental findings and theoretical interpretations have spurred intense debate over the electrical properties of DNA, the electronic properties of DNA still remain controversial, and the nature of the carriers responsible for DNA electrical conductivity is still under investigation. It has been demonstrated that both vacancies and electrons can migrate through the DNA helix over distances, as well as, results indicate that correlation effects are probably responsible for large hopping distances in DNA samples . Consequently, electrochemistry of nucleic acids and DNA modified electrodes may provide valuable insights into charge transfer processes and could be exploited in the design of electrochemical DNA‐based biosensors.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding experimental findings and theoretical interpretations have spurred intense debate over the electrical properties of DNA, the electronic properties of DNA still remain controversial, and the nature of the carriers responsible for DNA electrical conductivity is still under investigation. It has been demonstrated that both vacancies and electrons can migrate through the DNA helix over distances, as well as, results indicate that correlation effects are probably responsible for large hopping distances in DNA samples . Consequently, electrochemistry of nucleic acids and DNA modified electrodes may provide valuable insights into charge transfer processes and could be exploited in the design of electrochemical DNA‐based biosensors.…”
Section: Introductionmentioning
confidence: 99%
“…Guanines, which have the lowest ionization potentials of the four nucleobases, tend to trap the electron hole after a base-to-base charge transfer process through the stacked nucleobases, resulting from coupling between the overlapping π-orbitals (Giese, 2002). However, direct experimental measurements of long-distance hole transfer in DNA remain the subject of intense debate mainly due to the challenging experimental requirement of working at the nanoscale (Triberis & Dimakogianni, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…To accomplish our task, we developed a novel theoretical approach inspired by the eminent work of Apsley and Hughes [40] in combination with the GMCM [13,17,12,24,26] and references therein. In addition, we combined analytical work with numerical calculations.…”
Section: Resultsmentioning
confidence: 99%